2017
DOI: 10.1038/sc.2017.93
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of resilience among people who sustained spinal cord injury from the 2015 earthquake in Nepal

Abstract: More than half of Nepalese who sustained SCI from the 2015 earthquake in Nepal had not achieved a high level of resilience 2 years later. Gender was a significant determinant of resilience. The results highlighted the importance of providing appropriate intervention and allocating continuing support to the Nepalese people with SCI. A further longitudinal study is recommended to determine predictive factors of the dynamic nature of resilience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Strong social support encompasses protective, compensatory, and challenge-related coping-concept strategies (Ahern et al, 2006; Bhattarai et al, 2018; Edward, 2013; Machida et al, 2013; Monden et al, 2014; Shin et al, 2012; Spratling & Weaver, 2012). The ability to adapt to injury and resultant changes (Ahern et al, 2006; Bhattarai et al, 2018; Edward, 2013; Hunter & Chandler, 1999; Jones et al, 2019; Kornhaber et al, 2018; Machida et al, 2013; McDonald et al, 2019; Monden et al, 2014; Spratling & Weaver, 2012), and the act of serving as a role model or inspiring others (Monden et al, 2014), are key challenge-related coping-concepts strategies. Salient protective coping-concept strategies include spirituality (Bhattarai et al, 2018; Jones et al, 2019; Monden et al, 2014); psychological strength (Monden et al, 2014; Tusaie & Dyer, 2004); and perspective (Garmezy, 1993; Monden et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Strong social support encompasses protective, compensatory, and challenge-related coping-concept strategies (Ahern et al, 2006; Bhattarai et al, 2018; Edward, 2013; Machida et al, 2013; Monden et al, 2014; Shin et al, 2012; Spratling & Weaver, 2012). The ability to adapt to injury and resultant changes (Ahern et al, 2006; Bhattarai et al, 2018; Edward, 2013; Hunter & Chandler, 1999; Jones et al, 2019; Kornhaber et al, 2018; Machida et al, 2013; McDonald et al, 2019; Monden et al, 2014; Spratling & Weaver, 2012), and the act of serving as a role model or inspiring others (Monden et al, 2014), are key challenge-related coping-concepts strategies. Salient protective coping-concept strategies include spirituality (Bhattarai et al, 2018; Jones et al, 2019; Monden et al, 2014); psychological strength (Monden et al, 2014; Tusaie & Dyer, 2004); and perspective (Garmezy, 1993; Monden et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen participants (19.5%) had chronic disease which included hypertension ( n = 7), asthma, gout, and gastrointestinal problems. The reported SCI-related complications were pain ( n = 66), spasticity ( n = 21), pressure injury ( n = 10), and urinary tract infection ( n = 8) [ 32 ]. Table 1 shows the demographics and injury-related characteristics of the participants.…”
Section: Resultsmentioning
confidence: 99%
“…Initially we would like to thank Bhattarai et al [1] for sharing their interesting findings about the determinants of resilience among people with spinal cord injury. Although their study provided valuable information about purposeful care delivery to people with spinal cord injury who are at risk for mental health problems, there are some concerns over outcome measurement and findings in the study.…”
mentioning
confidence: 99%
“…Finally, as the study of Bhattarai et al [1] provides valuable information about resiliency determinants among clients with spinal cord injuries; it is suggested that the above-mentioned points be considered in future studies in order to enhance more evidence-based results.…”
mentioning
confidence: 99%